Remembering the Forgotten Past: A Case Study of Bali's First Governor, Anak Agung Bagus Sutedja - Nyoman Wijaya (Center for Southeast Asian Social Studies (CESASS), 2019)
This article explores the way forgetting and remembering a dark past takes place in Balinese society. To do so, it takes the case of Anak Agung Bagus Sutedja, the first Governor of Bali, who was appointed in 1959 but 'disappeared' in 1965 or 1966. He has been systematically forgotten by Balinese society and, more specifically, by and within the academic community of Udayana University. Applying a historical approach, this article argues that the process of forgetting in the community is deeply entangled with the New Order's embodied official narratives about the 1965 tragedy